Improving Numeracy Skills in Children Aged 4-5 Years Through Dough Play Activities: A Classroom Action Research - Nisrina Farida (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: Numeracy is a foundational cognitive skill for young children that underpins subsequent academic achievement. However, conventional rote-based instruction methods have proven ineffective in fostering genuine number sense in early childhood settings. Purpose: This study aimed to investigate whether dough play activities could improve the numeracy skills of 4–5-year-old children at TK Al-Muhadjirin 2, East Bekasi, Indonesia. Materials and methods: A Classroom Action Research (CAR) design was employed across two cycles (10 sessions total), involving 12 children aged 4–5 years. Numeracy performance was assessed using structured observation instruments covering number concept, number symbol recognition, number sequencing, number matching, number-to-object correspondence, and numeral writing. Data were analyzed using percentage calculations and qualitative thematic analysis. Results: Mean numeracy scores improved from 54% (pre-intervention) to 74% at end of Cycle I, and to 82% at end of Cycle II, exceeding the predetermined success threshold of 71%. All 12 participants demonstrated measurable improvement across all assessed numeracy indicators. Conclusions: Dough play activities constitute a developmentally appropriate, multisensory pedagogical intervention that significantly enhances numeracy competence in early childhood. The tactile-kinesthetic engagement afforded by dough manipulation supports concrete understanding of number concepts, facilitating the transition from enactive to symbolic mathematical reasoning.